Evaluation the efficiency of nursing performance depended on standards of( W.H.O )Practical research in medical city office hospitals - عبد ناظم جواد; اعيادة عامر جبار (Journal of Economics and Administrative Sciences, 2016)
This research a mining at evaluation the efficiency of the nursing performance depended on standards of W.H.O. via application standards of W.H.O on the nursing personnel in medical city office, in light of it, it has design world evaluation list, and a sample was chosen from the nursing personnel in given researched the organization whom they are evaluated according to the standards of W.H.O for the nursing performance included of ten standards, divided in to 45 question , besides the evaluation list, the researcher get assistance of some tools of collection information via actual checking and personal interviews, a number of statistical means were used to manipulate these information such as the mean. Standard deviation, percentage, hypothetic mean, and liaison of perason was used and Spare man correction equation and Alfa coefficient for the external adhesion. And depending on research variables standards and indentifying them , and examine the liaison relation and the effect and differences among them, the researcher has reached to a number of conclusions most important of which non-existence of organizational standards in the researched organization in the nursing performance , and non-existence of administration experience in most of the nursing personnel via making decision and the ability of to form team and to solve the problems and the organization point of view was translated.